Argentina : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Argentina. (IMF Staff Country Reports; Country Report, 2016)
An inherited legacy of imbalances. Upon taking office in December last year, Argentina's new government faced pervasive macroeconomic imbalances, microeconomic distortions, and a weakened institutional framework. These encompassed unsustainably high consumption levels, historically low levels of investment, and large fiscal deficits financed by money creation, which led to high inflation. Distortions at the micro level included an extensive network of administrative controls (for example, trade barriers, foreign exchange restrictions, and price controls) and a business environment that eroded competitiveness and undermined medium-term growth. There was also an important weakening of the institutional framework for economic policymaking, perhaps most evident in the loss of credibility of the national statistics agency.